Answer: 28
Step-by-step explanation:
Simplifying
2x + 16 = 3x + -12
Reorder the terms:
16 + 2x = 3x + -12
Reorder the terms:
16 + 2x = -12 + 3x
Solving
16 + 2x = -12 + 3x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-3x' to each side of the equation.
16 + 2x + -3x = -12 + 3x + -3x
Combine like terms: 2x + -3x = -1x
16 + -1x = -12 + 3x + -3x
Combine like terms: 3x + -3x = 0
16 + -1x = -12 + 0
16 + -1x = -12
Add '-16' to each side of the equation.
16 + -16 + -1x = -12 + -16
Combine like terms: 16 + -16 = 0
0 + -1x = -12 + -16
-1x = -12 + -16
Combine like terms: -12 + -16 = -28
-1x = -28
Divide each side by '-1'.
x = 28
Simplifying
x = 28
Answer:
The value of x is 2
Step-by-step explanation:
<h3><u>Given</u>;</h3>
<h3><u>To Find</u>;</h3>
Now,
tan 27 = 1/x
0.5 = 1/x
x = 1/0.5
x = 2
Thus, The value of x is 2
<u>-TheUnknownScientist 72</u>
Answer:
x =0
Step-by-step explanation:
4+5e^x+2 =11
Combine like terms
6 + 5e^x =11
Subtract 6 from each side
6-6 + 5e^x =11-6
5 e^x = 5
Divide by 5 on each side
5 e^x /5 = 5/5
e^x = 1
Take the natural log on each side
ln (e^x) = ln(1)
x = ln(1)
x =0
Answer:
C. 11.8
The answer is exactly <em>11.77</em>. But when rounded it is <em>11.8</em>.